Mengenal Data Ekstrim dan Distribusinya - Indriati Bisono (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2011)
People adopt many definitions for extremes. One such definition is that extremes are simply the upper tail data. In this paper we briefly review the types of upper tail data, the limiting distribution of extreme values, the analysis and the model diagnostics. We also provide a simple example of fitting generalized extreme values (GEV) for climate extremes